2015
DOI: 10.1007/s13277-015-4538-0
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory B cells contribute to the impaired antitumor immunity in ovarian cancer patients

Abstract: Multiple factors in the tumor microenvironment were found to inhibit antitumor adaptive immune responses, allowing tumor persistence and growth. In this study, ascites from ovarian cancer patients were collected. We observed that a population of interleukin-10(+) B (IL-10(+) B) cells was preferentially enriched in the ascites. This population was associated with naive B cell phenotype or IgM or class-switched memory B cell phenotypes. The frequencies of IL-10(+) B cells were negatively correlated with the freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 32 publications
4
76
0
Order By: Relevance
“…Increased B-cell subset may lead to poor clinical prognosis in NSCLC. Similar results are also found in ovarian cancer [61]. The population of B10 cells is preferentially enriched in ascites, and their frequency is positively correlated with ovarian cancer severity.…”
Section: Negative Effect Of B Lymphocytes On the Immune Systemsupporting
confidence: 79%
See 2 more Smart Citations
“…Increased B-cell subset may lead to poor clinical prognosis in NSCLC. Similar results are also found in ovarian cancer [61]. The population of B10 cells is preferentially enriched in ascites, and their frequency is positively correlated with ovarian cancer severity.…”
Section: Negative Effect Of B Lymphocytes On the Immune Systemsupporting
confidence: 79%
“…As a result, Bregs may inhibit T cell proliferation through cell-to-cell contact, thereby leading to anergy or apoptosis [75]. Moreover, B10 cells from the ascites of ovarian tumor [61] can suppress the IFN-γ production of CD8 + T cells. When co-cultured CD8 + T cells with autologous blood B cells or ascitic B cells, the co-cultured group demonstrates significantly decreased IFN-γ production.…”
Section: Negative Effect Of B Lymphocytes On the Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Within this same study, Zhou et al demonstrated that IL10 + TIL-Bs positively correlated with increased Tregs and decreased survival. B cell–mediated immunoregulation has also been shown using B and T cells isolated from the ascites of ovarian cancer patients (38). However, studies of TIL-Bs from NSCLC patients have not yet been published.…”
Section: Introductionmentioning
confidence: 97%
“…To date, there is a controversy, since several studies suggest that TIBs are protective [164][165][166] , while others indicate that Bregs are increased in patients with solid tumours, which is associated with increased aggressiveness and inferior patients' outcome [167][168][169][170][171] . In lymphoid malignancies, the anti-tumour immune responses are suppressed by malignant B cells that 'perform' as Bregs via the expression of suppressive ligands [172][173][174] .…”
Section: Tumour-infiltrating B Cellsmentioning
confidence: 99%